Journals strategy to improve writing skills for agropecuaria major students - Bodero Alvia, Joan Josue (2023)
Journals have constituted an important element when developing writing skills. The present study analyzes journals as a strategy to improve writing skills for Agropecuaria major participants. To carry out this research, the qualitative method and phenomenological study were applied. The data was gathered from interviews to a group of of 7 participants belonging to the Agropecuaria major 7/1 of the Universidad Estatal Península de Santa Elena, located in Santa Elena. The questionnaire was the only data collection instrument sample. The interviewees, as part of the information collected, expressed their agreement of the use of journals; however, they also revealed the lack of time to write journals constitutes an obstacle to the development of writing skills. Finally, the development of writing skills is not far from a constructivist process, since all participants need to learn something new, this is the English language, but supported by their own experiences.